Relationship between low birth weight in children and early Childhood caries – a systematic review - ANITHA JAYAKUMAR; DEEPA GURUNATHAN (International Journal of Pharma and Bio Sciences, 2017)
WHO defined low birth weight (regardless of the gestational age ) as weighing less than 2500g.. Low birth weight neonates are further subdivided into very low birth weight infants, with birth weights less than 1500g and extremely low birth weight infants, with birth weights less than 1000g. Early childhood caries due to malnutrition is still a common dental health problem in developing countries. Dental caries can gradually reduce a child’s ability to gain weight, which may get reversed after complete oral rehabilitation. The aim of this systematic review was to analyze the existing literature on the relationship between the low birth weight in children and the early childhood caries. The databases of PubMed, Cochrane, LILACS, Science direct, Metapress and SIGLE and hand search were done upto January 2016 for the related topic. Clinical studies which evaluated the relationship between low birth weight in children and the early childhood caries were included in this review. The systematic search revealed eighty seven articles of which four met inclusion criteria. With the available of evidence in literature, four studies were found to have relationship between ECC and the low birth weight in children. Among the four studies included, three studies were of good quality and in the three studies, two studies stated there is statistical significance in the relationship between ECC and lowbirthweight in children. Therefore it is concluded that there is a need of clinical studies on the relationship of ECC and the low birthweight in children.